KEKERASAN PEREMPUAN DALAM PERSPEKTIF HUKUM DAN SOSIOKULTURAL - Amalia, Mia (Sekolah Tinggi Hukum Bandung, 2011)
Every citizen of Indonesia deserves to obtain right to feel secured and free from violence according to the philosophy of Pancasila and the 1945 Constitution; that any violence, especially domestic violence is a kind of violence against human rights, and it is categorized as a crime against dignity of humanity and a discrimination that should be abolished; most of the victims of domestic violence are women, and they should obtain more serious attention and protection from the government, or society in order to avoid threat and violence, torture, or harrashment of dignity of humanity.Keywords: violence; humanity; human rights